Duan-Lolat Tradition In Traditional Marriage Of The Tanimbar Community: Ethnographic Study of Traditional Marriage in Latdalam Village, Tanimbar South District, West Southeast Maluku Regency - Dasfordate, Aksilas; Sholahuddin, Agus; Ngarawula, Bonaventura (Technium Social Sciences Journal, 2020)
The Tanimbar people certainly have customs, traditions, and habits that have been preserved from generation to generation. The Duan and Lolat systems represent customs and traditions, which are still present throughout the Tanimbar archipelago. In that context, as part of the Tanimbar community, the people of Latdalam village, South Tanimbar district, West Southeast Maluku district who inhabit the west coast of Yamdena Island also use the Duan and Lolat traditions in various aspects of life, both political, economic and socio-cultural life. The main objective of this research is to describe and analyze the process of the formation of Duan and Lolat traditions in the traditional marriage of Latdalam villagers in the South Tanimbar district, West Southeast Maluku Regency. The approach used in this research is to use a descriptive-qualitative approach. The research location is Latdalam Village, South Tanimbar district, West Southeast Maluku Regency. Informants in this study consisted of; the Latdalam village government; the Church, namely religious leaders who know and understand the traditions of Duan and Lolat in the marriage customs of the Latdalam community; Duan and Lolat parties that involve two families in carrying out traditional marriages. Data collection techniques through observation, interviews, and documentation studies. The research instrument is the researcher himself as the main instrument. The results obtained from this study are as follows: (1). In the life of the people of Tanimbar, West Southeast Maluku Regency, a kinship value known as Duan and Lolat has been maintained for a long time. The Duan and Lolat traditions are applied in various aspects of life, including marriage. (2). The process towards a traditional marriage based on the Duan and Lolat traditions in the Latdalam Village community, Tanimbar Selatan District, West Southeast Maluku Regency. (3). The traditions of Duan and Lolat in traditional community marriages in Latdalam village contain religious or belief values, art, language, and law. This study recommends further research on the wars of the West Southeast Maluku Regency government, especially the District Tourism Office, in designing work programs to promote the Duan and Lolat traditions as local wisdom.